#### Answer

b = 7

#### Work Step by Step

8 - (3 + b) = b - 9
Use the distributive property:
8 - 1(3) + -1(b) = b - 9
Simplify:
8 - 3 - b = b - 9
To get the variable (b) on one side of the equation, add b to the right side of the equation. This also removes b from the left side of the equation.
8 - 3 - b + b = b - 9 + b
Simplify to get:
8 - 3 = 2b - 9
Add 9 to both sides of the equation.
8 - 3 + 9 = 2b - 9 + 9
Simplify to get:
14 = 2b
Divide both sides by 2:
$\frac{14}{2}$ = $\frac{2b}{2}$
7 = b
Check:
To check whether 7 is the correct answer, replace b with 7 in the original equation and solve.
8 - (3 + b) = b - 9
8 - (3 + 7) = 7 - 9
8 - 3 - 7 = 7 - 9
-2 = -2